Facet-controlled synthesis and morphological evolution of Cu2O microcrystals. Issue 16 (29th March 2022) - Kim, Eung-Dab; Cho, Young-Sik; Huh, Young-Duk
Abstract : Cu2 O microcrystals were prepared through reduction of Cu 2+ ions by glucose in an alkaline aqueous solution. Abstract : Cu2 O microcrystals were prepared through reduction of Cu 2+ ions by glucose in an alkaline aqueous solution. Various shapes of Cu2 O microcrystals were obtained by adjusting the reaction temperature, NaOH concentration, and glucose amount. The morphology of the Cu2 O crystals changed from pure octahedra to beveled cubes via corner-truncated octahedra and truncated cuboctahedra as the reaction temperature was increased. These changes arose because of the growth of the 100 and 110 facets at the expense of the 111 facet with increasing reaction temperature. The morphological evolution of Cu2 O crystals from truncated cuboctahedra to corner-truncated octahedra via corner- and edge-truncated octahedra was observed with increasing NaOH concentration, which occurred because of the growth of 111 facets at the expense of 100 facets during simultaneous growth in the early stage and at the expense of 110 facets in the late stage. The morphological evolution of the Cu2 O crystals from truncated cuboctahedra to pure cubes via beveled cubes and corner-truncated cubes was observed with increasing amount of d -(+)-glucose. The 110 and 111 facets were gradually replaced by 100 facets with increasing amount of d -(+)-glucose.